PENINGKATAN EKONOMI KELOMPOK TANI “RUKUN TANI” KAMPUNG MARGA MULYA MELALUI PEMBUATAN PAKAN TERNAK SAPI MENGGUNAKAN CHOPPER - Aldisa Arifudin; Leonora Puspa (Musamus Devotion Journal, 2023)
Making Cattle Feed Using a Chopper is a community service activity in a community partnership program that aims to assist breeders in making efficient cattle feed. Farmers are given assistance on how to make animal feed using a chopper with grass ingredients that are usually given to cattle. Making feed using a chopper can combine other feed ingredients into one such as grass, banana stems, corncobs, and others. With this feed, it is hoped that the cattle will fatten up faster, which of course will affect sales so that it can directly improve the farmer's economy. The implementation of this program will go through several stages including activity socialization, technology preparation, technology workshops, technology implementation, evaluation, publication, and final reporting.